Exploratory study on the impact of Ganoderma australe extract on gut microbiota and immune gene expression in honey bees exposed to Vairimorpha ceranae - Sarah Zuern; Bella Romero; Carlos Spichiger; Leandro Ortiz; Alejandro Jerez; Esteban Basoalto; Max Emil Schön; Sigisfredo Garnica (PLoS ONE, 2026)
The microsporidium Vairimorpha ( Nosema ) ceranae is an emerging threat to honey bees ( Apis mellifera ), known to disrupt gut microbiota and suppress immune responses, potentially contributing to colony losses. Fungal extracts have recently gained interest as sources of bioactive compounds with antimicrobial and immunomodulatory potential. In this study, we explored the effects of different dietary supplements—sugar syrup, HiveAlive™, and a novel Ganoderma australe extract (GanoBee)—on gut bacterial composition and immune-related gene expression in honey bees subjected to experimental exposure to V. ceranae 1 x 10 4 spores per bee. The GanoBee diet altered the gut microbiota, notably reducing the relative abundance of Rhizobiaceae ( Bartonella apis ) and increasing Frischella compared to other treatments. While alpha diversity was not significantly affected by diet or exposure to V. ceranae , beta diversity differed significantly in bees fed with GanoBee. Additionally, the expression of the antimicrobial peptide genes abaecin and hymenoptaecin was elevated in both exposed and unexposed bees fed with GanoBee, depending on the sampling day. However, the establishment of V. ceranae infection appeared limited, likely due to low spore viability, and mortality in control bees was higher than expected. The low Vairimorpha ceranae infection levels observed in this study are likely attributable to reduced spore viability caused by storage conditions and/or suboptimal environmental conditions within the laboratory cages. Post hoc analyses indicated that the high viscosity of GanoBee-supplemented diets likely contributed to the elevated bee mortality observed, underscoring a critical limitation of the experimental design related to diet formulation and delivery method. These physical factors complicate the interpretation of treatment efficacy and highlight the importance of optimizing feeding protocols to avoid confounding effects. Despite these constraints, GanoBee demonstrated promising potential as a modulator of gut microbiota composition and immune-related gene expression, supporting the need for further research under improved and carefully controlled experimental conditions.